Positioning and Anesthesia Challenges In a Morbidly Obese Patient Undergoing Cervical Spine Surgery - Keyuri Popat; David Z. Ferson; Brian Galle; Roxana Grasu; Gisela Sanchez; Claudio Tatsui; Lawrence Rhines (Research and Practice in Anesthesiology, 2016)
Background Context: By itself, the perioperative anesthesia management of morbidly obese patients is challenging; this task is further complicated when such patients have to be placed in the prone position for surgery. In these cases, challenges may include positioning, intubation and ventilation. Purpose: Herein, we describe the safe perioperative anesthesia care of a morbidly obese patient undergoing cervical spine surgery for an enlarging schwannoma. Study Setting: Morbidly obese patient care at a tertiary cancer institute. Patient Sample: Single case report. Methods: Describing the preparation and planning for this complex case and the perioperative care of a patient with several comorbidities. No conflict of interest to report for any of the authors. Results: Good patient outcome. Conclusion: Careful multi-disciplinary planning facilitates, good patient outcome, given the challenging nature of the case. Highlighting the use of a trial run in the operating prior to the day of surgery.